Adoption of cassava improved modern varieties in the Cauca department in Colombia using DNA fingerprinting - Floro, Victorino O.; Labarta, Ricardo Antonio; Becerra López Lavelle, Luis Augusto; Martínez, Jose M.; Ovalle, Tatiana M.; Rivera Vasco, Tatiana Carolina; Álvarez, Diego A.; Calle, F.; Ocampo, John (International Center for Tropical Agriculture, 2020)
This dataset provides a description of cassava farmers collected in the Colombian Cauca Department during 2014-2015. The survey was implemented using a structured questionnaire administered among 217 households, collecting data at both household and plot level. Survey information includes household socio-demographic characteristics, cassava management practices (e.g. improved variety and other input use, etc.) and cassava production and utilization. Additionally, it was collected crop samples for DNA fingerprinting. The dataset contains numeric, categorical and string variables.